Wnt Inhibition Sensitizes PD-L1 Blockade Therapy by Overcoming Bone Marrow-Derived Myofibroblasts-Mediated Immune Resistance in Tumors - Huang, Tinglei; Li, Fuli; Cheng, Xiaojiao; Wang, Jianzheng; Zhang, Wenhui; Zhang, Baiwen; Tang, Yao; Li, Qingli; Zhou, Cong; Tu, Shuiping (Frontiers in Immunology, 2021)
Cancer-associated fibroblasts (CAFs) has been recognized as one cause of tumor resistance to immune checkpoint blockade therapy, but the underlying mechanisms still remain elusive. In the present study, we successfully established a bone marrow-derived CAF (BMF) and tumor cells mixed tumor model and found that BMF-mixed tumor xenografts were resistant to anti-PD-L1 antibody therapy compared to single tumor xenografts. We found that BMFs overexpressed PD-L1 in a co-culture system of BMFs and tumor cells, whereas the PD-L1 expression did not change in cancer cells. Knock-out of the PD-L1 in BMFs rescued the sensitivity of BMF-mixed tumor xenografts to PD-L1 blockade therapy. We further identified that cancer cells stimulated BMFs to express PD-L1 via activating Wnt/β-catenin signaling pathway using microarray system. Inhibition of Wnt/β-catenin signaling by Wnt/β-catenin signaling inhibitor XAV-939 and Wnt-C59 blocked the upregulation of PD-L1 expression in BMFs in the co-cultured system. Moreover, the combination administration of XAV-939 significantly enhanced therapeutic outcome of PD-L1 blockade therapy. In summary, our study demonstrated that Wnt inhibition augmented PD-L1 blockade efficacy by overcoming BMF-mediated immunotherapy resistance.